ANALISIS YURIDIS PEMBUKTIAN TINDAK PIDANA JUDI ONLINE MENURUT UNDANG-UNDANG NO. 11 TAHUN 2008 TENTANG INFORMASI DAN TRANSAKSI ELEKTRONIK - Parlindungan Twenti Saragih; Syafruddin Kalo; Mahmud Mulyadi; Edi Yunara (USU LAW JOURNAL, 2018)
ABSTRACT The online gambling crime initially took place in 1994 of Antigua and Barbuda countries in the Caribbean which passed freedom of trade and processing legislation, which then allowed the licensing of organizations to build easy online casino openings. Before online casinos, the first fully-functioning gambling software was produced by Mann's software company called microgaming. The use of the software is then guaranteed security by a security company for software called Cryptologic. Given these steps gambling transactions via the internet can be done safely and became the embryo of the first online casino in 1994. In Indonesia gambling is a crime or a criminal offense so that every involved in it will be subject to criminal sanctions. The article governing gambling is Article 303 bis para (1) of the Criminal Code (KUHP). Furthermore, if a person engages in or engages in online gambling, the articles imposed do not refer to the Criminal Code but refer to Article 27 of Law No. 23/1999. 11 Year 2008 About Information And Electronic Transactions, The emergence of online gambling offenses is certainly very difficult to prove because it can be ascertained the investigators are not all have the ability in information and technology (IT). This resulted in the difficulty of the disclosure of online gambling that continues to grow in the community. Online gambling is now not only limited to sites that really provide online gambling but to hide the trail of sites that are pure games not for gambling is also used as a means to smooth the business of online gambling. For example, the card games contained in facebook are often also used or used for online gambling. Based on the above description, it is interesting to discuss the legal issues entitled "Juridical Analysis of Proof of Online Gambling Crime According to Law no. 11 Year 2008 About Information And Electronic Transactions.   Keyword: Online gambling and electronic transactions